Impact of pleural thickness on the sensitivity of computed tomography scan-guided cutting-needle pleural biopsy in diagnosing unexplained exudative pleural effusion - Rui Xu; Ling Zuo; Chiyong Yang; Li Jiang; Ying Liu; Ping Fan; Kaige Wang; Dan Liu (Respiratory Research)
Abstract Background In most cases, patients with pleural effusion require a pleural biopsy to confirm the diagnosis, due to the low diagnostic sensitivity of thoracentesis. Among the different biopsy modalities, real time computed tomography scan-guided cutting-needle pleural biopsy (CT-CNPB) ensures high sensitivity and accessibility. However, there is no study investigating the difference in the diagnostic sensitivity of CT-CNPB for lesions with variable pleural thickness in effusions of different types. Methods Of the 303 patients who underwent CT-CNPB, 218 met the eligibility criteria and were retrospectively analyzed from November 2021 to June 2024. Patients were divided into malignant pleural effusion (MPE), tuberculosis pleural effusion (TPE), and non-tuberculous benign pleural effusion (BPE) groups according to the diagnosis with a minimum follow-up of 6 months. Pleural thickness was defined as the length of the portion of the puncture needle that passes through the thickened parietal pleura or the pleural lesion (nodule/mass). In further analysis, we compare the differences in sensitivity between subgroups with different pleural thicknesses in each group. Results The overall diagnostic sensitivity is 74.3%. The sensitivity in MPE, TPE, and BPE is 75.7%, 78.6%, and 67.8%, respectively. There was a significant difference in sensitivity between the < 5 mm and ≥ 5 mm groups in MPE and BPE groups but was not observed in the TPE group. In the further analysis, there was a significant difference in sensitivity between < 3 mm and 3–5 mm groups in TPE (p = 0.046) and a significant difference in sensitivity between 3 and 5 mm and 5–10 mm groups in MPE (p = 0.017), but a significant difference was not observed in BPE group. Conclusion CT-CNPB may serve as a preferred diagnostic approach in suspected TPE with pleural thickening ≥ 3 mm and suspected MPE with thickening ≥ 5 mm on chest CT. Where MT is unavailable, CT-CNPB is a viable alternative for suspected MPE or TPE patients with pleural thickening, nodularity, or mass lesions observed on CT. However, in suspected BPE, CT-CNPB alone is often insufficient; integrated clinical, laboratory, and imaging evaluation remains essential.